Perspectives of High School Teachers on the Role of Values Education in the Curriculum: A Qualitative Study at Asir District, Saudi Arabia - Alwadai, Mesfer Ahmed Mesfer; Alhaj, Ali Albashir Mohammed (Technium Social Sciences Journal, 2023)
The current study covets to investigate the perspectives of Saudi high school teachers on the role of values education in the curriculum in inculcating certain moral values among high school students in the Asir district. Also, the study purports to probe the degree to which the role of values education in the high school curriculum imbues unequivocal moral values among high school students from the perspectives of their teachers. The qualitative study method was employed by two researchers because qualitative research is a line of research that probes and stipulates a better understanding of real issues. Moreover, the two researchers adopted one of the most appropriate tools to attain the objectives of the study. It is an opinion poll of fourteen items concentrated on the perspectives of Saudi high school teachers in the Asir district. The study results showed that high school teachers perceive the high school curriculum as having a pivotal role in stilling values education and moral improvement among the students. The study results also displayed that values education is the most commonly responding and spontaneous and embedded in diurnal educational life with a focus on students’ diurnal behavior in high school, and relatively or usually unconsciously fulfilled.